Neuroprotective Drugs in Infants With Severe Congenital Heart Disease: A Systematic Review - Stegeman, Raymond; Lamur, Kaya D.; van den Hoogen, Agnes; Breur, Johannes M. P. J.; Groenendaal, Floris; Jansen, Nicolaas J. G.; Benders, Manon J. N. L. (Frontiers in Neurology, 2018)
Background Brain injury is a fundamental problem in infants with severe congenital heart disease (CHD) undergoing neonatal cardiac surgery with cardiopulmonary bypass (CPB). An impaired neuromotor and neurocognitive development is encountered and associated with a reduction in quality of life. New neuroprotective drugs during surgery are described to reduce brain injury and improve neurodevelopmental outcome (NDO). Therefore, our aim was to provide a systematic review and best-evidence synthesis on the effects of neuroprotective drugs on brain injury and NDO in CHD infants requiring cardiac surgery with CPB. Methods A systematic search was performed in PubMed, Embase and the Cochrane Library (PRISMA statement). Search terms were ‘infants’, ‘CHD’, ‘cardiac surgery’, ‘CPB’ and ‘neuroprotective drug’. Data describing the effects on brain injury and NDO were extracted. Study quality was assessed with the Cochrane Risk of Bias Tool. Two reviewers independently screened sources, extracted data and scored bias. Disagreements were resolved by involving a third researcher. Results The search identified 293 studies of which 6 were included. In total 527 patients with various CHD participated with an average of 88 infants (13-318) per study. Allopurinol, sodium nitroprusside (SNP), erythropoietin (EPO), ketamine, dextromethorphan and phentolamine were administered around cardiac surgery with CPB. Allopurinol showed less seizures, coma, death and cardiac events in hypoplastic left heart syndrome (HLHS) infants (OR:0.44;95%-CI:0.21-0.91). SNP resulted in lower post CPB levels of S100ß in infants with transposition of the great arteries after 24 (p<0.01) and 48 hours (p=0.04) of treatment. EPO, ketamine and dextromethorphan showed no neuroprotective effects. Phentolamine led to higher S100ß-levels and cerebrovascular resistance after rewarming and at the end of surgery (both p<0.01). Risk of bias varied between studies, including low (SNP, phentolamine), moderate (ketamine, dextromethorphan) and high (EPO, allopurinol) quality. Conclusions Allopurinol seems most promising for future trials in CHD infants to reduce brain injury given the early neuroprotective effects in HLHS infants. Larger well-designed trials are needed to assess the neuroprotective effects of SNP, EPO, ketamine and dextromethorphan. Future neuroprotective studies in CHD infants should not only focus on the perioperative period, however also on the perinatal period, since brain injury already exists preoperatively.